Improving a Course Design through Classroom Action Research - Kasihani K.E Suyanto (Universitas Negeri Malang, 2016)
Through two cycles of actions course designed for preparing teachers of English for primary education has been revised. The objectives are to improve the presentation of the course and to meet the students' need and satisfaction. The result shows that according to the students the course has become more interesting and they admit that they have learned a lot from the course activities. By the end of the semester the course design has been reconstructed based on the result of the actions. Group-discussions, students involvement in material and media selection, adaptation and development are the main characteristics of the revised EYL course